Impact of Training & Development on Organizational Performance: An Analysis - Panda, Sitansu (ESB Business School, 2016)
Training & Development (T&D) is a function of human resource management. It is concerned with the development of individual employees and effective working teams to improve their performance through enhancing their competencies. The purpose of this study is to investigate the impact of T&D on Organizational Performance (OP). Hypotheses have been formulated indicating association between T&D and Organizational Performance. In this light, the study examined a series of hypothesis. Relevent data have been collected from the respondents of a manufacturing company. Broadly three categories of T&D programmes viz; knowledge oriented, technical oriented and behavioural oriented trainings have been categorized for this research. The impact of each category of T&D programme on Organizational Perforamnce is evident and statistically significant.The results corroborate the outcomes of previous studies establishing a positive relationship between T&D and Organizational Performance.